Mental Health and Rheumatoid Arthritis: Toward Understanding the Emotional Status of People with Chronic Disease. (11th February 2019) - Ziarko, Michał; Siemiątkowska, Katarzyna; Sieński, Michał; Samborski, Włodzimierz; Samborska, Joanna; Mojs, Ewa
Abstract : Introduction . Rheumatoid arthritis (RA) is a long-term disorder significantly impairing the somatic, emotional, and psychological functioning of its sufferers. Previous research has shown that affected individuals are characterized by an increased level of anxiety and depression. Currently, there are two main treatment schemes for RA; the first uses anti-inflammatory drugs, and the second utilizes biologic agents. This begs the question whether sufferers differ in intensities of pain, anxiety, and depression depending on the type of treatment and what the determinants of these affective states in patients treated using different methods are. Methods . The study comprised 85 patients affected by RA (including 57 receiving biologically inactive medication). Research participants filled out a set of questionnaires measuring levels of anxiety and depression, intensity of experienced pain, strategies of coping with pain, and ego resiliency. Results . The collected data was analyzed through intergroup comparisons, calculating simple correlation coefficients, developing and solving regression equations. The results imply that the choice of treatment differentiates the intensity of pain experienced by patients. Those receiving biologic agents reported lower levels of pain compared to those taking anti-inflammatory medication. It has also been noted that there are distinct configurations of conditions conducive to anxiety and depression in both anti-inflammatory and biologic agent groups. Discussion . The observed constellation of dependencies between variables indicates that the choice of treatment scheme differentiates pain levels. This confirms the assumption that pain intensity, coping strategies, and ego resiliency depend on the severity of anxiety and depression.